An expanded taxonomy of hepatitis C virus genotype 6: Characterization of 22 new full-length viral genomes - Li, Chunhua (Virology, 2015)
We characterized the full-length genomes of 22 hepatitis C virus genotype 6 (HCV-6) isolates: 10 from Vietnam (classified into subtypes 6e, 6h, 6p, 6r, 6s, and 6u), one from China (confirmed as a new subtype 6xd), and 11 from the Lao PDR (representing a new subtype 6xe plus eight novel variants). With these 22 new genomes, HCV-6 now has a diverse and extended taxonomic structure, comprised of 28 assigned subtypes (denoted 6a-6xe) and 27 unassigned lineages, all of which have been represented by full-length genomes. Our phylogenetic analyses also included many partially-sequenced novel variants of HCV-6 from Lao PDR. This revealed that Lao HCV isolates are genetically very diverse and are phylogenetically distributed in multiple lineages within genotype 6. Our results suggest that HCV-6 has been maintained in Laos, a landlocked country, since the common ancestor of genotype 6 and indicates historical dispersal of HCV-6 across Southeast Asia.